Food Commodity Development Strategy Towards Food Security in North Sumatra - Mutthaqin, Muhammad Satrya; Nasution, Yenni Samri Juliati; Lubis, Fauzi Arif (Dinasti Publisher, 2024)
Until now, North Sumatra's food security is still unstable. This condition gives a clear picture that North Sumatra Province experiences problems in the field of food security. Because of the position of the North Sumatra region's very strategic position, this province should be prosperous and independent in terms of food sources. This research aims to develop a policy strategy for the development of food commodities towards national food security. In supporting this research, SWOT, Interpretative Structural Modeling (ISM), and Balanced Score Card (BSC) methods are used. The SWOT method was used to formulate a strategy based on the identification of internal factors and external factors that had a significant influence based on the Mckinsey 7S and PEST models. Furthermore, the ISM method is used to determine strategy priorities. The BSC method is used to determine the implementation plan and mapping of the strategies formulated. The development of food commodity development policy strategies towards food security in North Sumatra based on the results of the research consists of 11 (eleven) main strategies consisting of Strategy SO-1,2,3, Strategy ST-1,2,3, Strategy WO-1,2,3 and Strategy WT-1,2. It is hoped that the eleven strategies resulting from this research can increase the development of food commodities in North Sumatra towards stable and sustainable food security.